Explore IDNLearn.com to discover insightful answers from experts and enthusiasts alike. Our platform offers comprehensive and accurate responses to help you make informed decisions on any topic.

3. For what values of [tex]\( m \)[/tex] is [tex]\( 2x^4 - mx^3 + 4x^2 + 2x + 1 \)[/tex] divisible by [tex]\( 1 - 2x \)[/tex]?

4. Use the factor theorem to determine whether [tex]\( x + \sqrt{2} \)[/tex] is a factor of [tex]\( 2\sqrt{2}x^2 + 5x + \sqrt{2} \)[/tex].


Sagot :

Let's break down and answer the questions step-by-step:

### Question 3: Determine for what [tex]\( d \)[/tex] the polynomial [tex]\( 1-2x \)[/tex] divides the polynomial [tex]\( 2x^4 - mx^3 + 4x^2 + 2x + 1 \)[/tex] where [tex]\( m=2 \)[/tex].

To determine if [tex]\( 1-2x \)[/tex] is a factor of the polynomial [tex]\( 2x^4 - mx^3 + 4x^2 + 2x + 1 \)[/tex] where [tex]\( m=2 \)[/tex], we will use the Factor Theorem. According to the Factor Theorem, [tex]\( x - a \)[/tex] is a factor of a polynomial [tex]\( P(x) \)[/tex] if and only if [tex]\( P(a) = 0 \)[/tex].

First, rewrite [tex]\( 1-2x \)[/tex] as [tex]\( -2x + 1 \)[/tex]. To use the Factor Theorem, we need to set [tex]\( -2x + 1 = 0 \)[/tex] and solve for [tex]\( x \)[/tex]:
[tex]\[ -2x + 1 = 0 \][/tex]
[tex]\[ x = \frac{1}{2} \][/tex]

Now substitute [tex]\( x = \frac{1}{2} \)[/tex] into the polynomial [tex]\( 2x^4 - mx^3 + 4x^2 + 2x + 1 \)[/tex]:
[tex]\[ P\left(\frac{1}{2}\right)= 2\left(\frac{1}{2}\right)^4 - 2\left(\frac{1}{2}\right)^3 + 4\left(\frac{1}{2}\right)^2 + 2\left(\frac{1}{2}\right) + 1 \][/tex]
Given [tex]\( m = 2 \)[/tex], substitute [tex]\( m \)[/tex] and compute:
[tex]\[ P\left(\frac{1}{2}\right)= 2\left(\frac{1}{2}\right)^4 - 2\left(\frac{1}{2}\right)^3 + 4\left(\frac{1}{2}\right)^2 + 2\left(\frac{1}{2}\right) + 1 \][/tex]
[tex]\[ = 2\left(\frac{1}{16}\right) - 2\left(\frac{1}{8}\right) + 4\left(\frac{1}{4}\right) + 2\left(\frac{1}{2}\right) + 1 \][/tex]
[tex]\[ = \frac{2}{16} - \frac{2}{8} + \frac{4}{4} + \frac{2}{2} + 1 \][/tex]
[tex]\[ = \frac{1}{8} - \frac{1}{4} + 1 + 1 + 1 \][/tex]
[tex]\[ = \frac{1}{8} - \frac{2}{8} + 3 \][/tex]
[tex]\[ = -\frac{1}{8} + 3 \][/tex]
[tex]\[ = 2.875 \][/tex]

For [tex]\( x = \frac{1}{2} \)[/tex] to be a root, [tex]\( P(\frac{1}{2}) \)[/tex] must be equal to 0. Since [tex]\( P(\frac{1}{2}) \neq 0 \)[/tex], thus [tex]\( 1-2x \)[/tex] is not a factor of the polynomial [tex]\( 2x^4 - mx^3 + 4x^2 + 2x + 1 \)[/tex] when [tex]\( m = 2 \)[/tex].

### Question 4: Use the factor theorem to determine whether [tex]\( x + \sqrt{2} \)[/tex] is a factor of [tex]\( 2\sqrt{2}x^2 + 5x + \sqrt{2} \)[/tex].

To determine if [tex]\( x + \sqrt{2} \)[/tex] is a factor of the polynomial [tex]\( 2\sqrt{2}x^2 + 5x + \sqrt{2} \)[/tex], we again use the Factor Theorem. According to the Factor Theorem, [tex]\( x - a \)[/tex] is a factor of a polynomial [tex]\( P(x) \)[/tex] if and only if [tex]\( P(a) = 0 \)[/tex].

Rewrite [tex]\( x + \sqrt{2} \)[/tex] as [tex]\( x - (-\sqrt{2}) \)[/tex]. We need to substitute [tex]\( x = -\sqrt{2} \)[/tex] into the polynomial:
[tex]\[ P(x) = 2\sqrt{2}x^2 + 5x + \sqrt{2} \][/tex]
[tex]\[ P(-\sqrt{2}) = 2\sqrt{2}(-\sqrt{2})^2 + 5(-\sqrt{2}) + \sqrt{2} \][/tex]
[tex]\[ = 2\sqrt{2}(2) - 5\sqrt{2} + \sqrt{2} \][/tex]
[tex]\[ = 4\sqrt{2} - 5\sqrt{2} + \sqrt{2} \][/tex]
[tex]\[ = 4\sqrt{2} - 4\sqrt{2} \][/tex]
[tex]\[ = 0 \][/tex]

Therefore, [tex]\( x + \sqrt{2} \)[/tex] is a factor of the polynomial [tex]\( 2\sqrt{2}x^2 + 5x + \sqrt{2} \)[/tex].